Analýza event marketingu studentské organizace - Ježková, Martina (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Tato diplomová práce se zabývá analýzou marketingové komunikace neziskové organizace se zaměřením na pořádání eventů a s tím související event marketing. Cílem analýzy je připravit podklady pro vytvoření a realizaci nového unikátního eventu, který doplní doprovodný program konkrétního projektu. Práce je rozdělena na část teoretickou, analytickou a návrhovou. Analytická část se zaměřuje na kulturní vyžití ve veřejném prostranství se zaměřením na studenty i širší veřejnost s cílem připravit unikátní event. Na základě této analýzy je navrhnut a začleněn konkrétní event do komunikačního mixu společnosti. Práce taktéž podrobně popisuje realizaci a zpětně hodnotí průběh akce.

This diploma thesis deals with the analysis of the marketing communication in non-profit organization focusing on organizing events and related event marketing. The aim of the analysis is to prepare the groundwork for the creation and implementation of new, unique event that will fill in the accompanying programme of a specific project. The work is divided into three parts: theoretical, analytical and proposal. The analytical part focuses on cultural activities in public spaces with focus on students and the public in order to prepare a unique event. Based on this analysis, the specific event is designed and incorporated into the communication mix of company. The diploma thesis also describes detailed implementation and assesses the whole progress of the event.
The Analysis of Event Marketing by Student Organisation
Keywords: Marketing; neziskový sektor; marketing neziskových organizací; event; event marketing; marketingová situační analýza; marketingové prostředí; SWOT analýza; SLEPT analýza; studenti; kultura; majáles.; Marketing; non-profit sector; marketing of non-profit organizations; event; event marketing; marketing situation analysis; marketing environment; SWOT analysis; SLEPT analysis; students; culture; majales.